2021
DOI: 10.1167/tvst.10.4.5
|View full text |Cite
|
Sign up to set email alerts
|

Association Between the Types of Posterior Staphyloma and Their Risk Factors in Pathological Myopia

Abstract: Purpose The purpose of this study was to investigate the relationship of posterior staphyloma (PS) types in pathological myopia (PM) with age, best-corrected visual acuity (BCVA), spherical equivalent (SE), axial length (AL), and myopic retinoschisis (MRS) using three-dimensional magnetic resonance imaging (3D-MRI) and optical coherence tomography (OCT). Methods This retrospective, cross-sectional study included 108 eyes of 59 patients with PM from the Henan Eye Institu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 36 publications
1
22
0
Order By: Relevance
“…Our results revealed that the location of RS was related to the shape of the staphyloma, and the retinoschisis was commonly seen in the macula if the staphyloma was type I or type II. This result was consistent with the data from a recent study (An et al, 2021). Several studies have indicated that MTM is more likely to occur and transform into severe stages in eyes with higher PSH (Jo et al, 2012; Ohsugi et al, 2019; Park et al, 2019).…”
Section: Discussionsupporting
confidence: 94%
“…Our results revealed that the location of RS was related to the shape of the staphyloma, and the retinoschisis was commonly seen in the macula if the staphyloma was type I or type II. This result was consistent with the data from a recent study (An et al, 2021). Several studies have indicated that MTM is more likely to occur and transform into severe stages in eyes with higher PSH (Jo et al, 2012; Ohsugi et al, 2019; Park et al, 2019).…”
Section: Discussionsupporting
confidence: 94%
“…However, its prevalence found by Curtin (7 eyes, 1.5%) 12 and Ohno-Matsui et al (5 eyes, 2.5%) 17 is lower than in recent series: 4.3%–6.9%. 23 , 25 , 28 Using multimodal imaging, including UWF fundus photos, PPS was even the most common subtype in Moreno et al series (62 eyes, 20%). 22 …”
Section: Background Definition Prevalencementioning
confidence: 89%
“…PS is mostly bilateral 22 , 25 and both eyes of bilateral cases have essentially the same ocular shape 10 , 12 , and PS subtype. 10 , 22 , 25 , 29 Moreno et al found that bilateral cases had longer AL and more severe PM than unilateral cases. 22 In unilateral cases, the AL-difference between the two eyes of the subjects was larger.…”
Section: Background Definition Prevalencementioning
confidence: 98%
See 1 more Smart Citation
“…Different types of PS can cause retinal lesions in different parts, resulting in varying degrees of vision or visual field loss ( Ohno-Matsui, 2014 ; Verkicharla et al, 2015 ; An et al, 2021 ; Lee et al, 2021 ). Many researchers have tried to propose a classification method for PS.…”
Section: Discussionmentioning
confidence: 99%